Role of Sex Chromatin on performance in the Arabi sheep: Salim Omar Raoof1, Dlpak Birkhader1, Sirod Sami Yahya1 and Younis Ahmad Sheakh Mohamad2 - Raoof, Salim Omar (The Iraqi Journal of Veterinary Medicine, 2017)
This study was conducted on 122 Arabi sheep belonged to private flock in Erbil plain Kurdistan region- Iraq, from July/ 2014 to August/ 2015 for studying the role of sex chromatin on daily milk production, total milk production, lactation period, fertility rate, prolificacy, birth weight and fertilizes estrous sequences. The repeatability for the studied traits were estimated. The ratio of sex chromatin shapes drum stick, sessile nodule, tear drop and small club were 23.37%, 60.22%, 8.54% and 7.87% respectively.The overall means of daily milk production, total milk production, lactation period, birth weight, fertilize estrous sequences, fertility rate, and Prolificacy were 814.65 g 81.49 kg 103.53 day, 78.10%, 1.60, 3.84 kg and 1.50 respectively. Sex chromatin shapes had significant (P<0.05) effect on all traits studied. The results revealed that the estimation of the Repeatability coefficient for daily milk production was 0.42. It was concluded from this study that production traits (milk production and birth weight) and reproduction (fertility rate, prolificacy and fertilize estrous sequences) performance of Arabi sheep were significantly affected by the shapes and percentage of sex chromatin distribution and measurements. The sex chromatin shapes could be used as a tool for early selection of the elite individuals.